Conducting Educational Intervention Research in General Practice: from Design to Publication - ZOU Chuan, OU Jianming, ZENG Xin, PENG Tao, ZHOU Yan, XIAO Chunyao, TAO Hongxia, CHEN Qingqi, LIN Kai (Zhongguo quanke yixue)
With the development of primary care in China, nearly 400 000 general practitioners will be trained in China in the next 10 years. The training of competent general practitioners is of vital importance, which requires general practice (GP) educators to explore a large number of evidence-based GP education concepts, methods, and contents that are applicable to China. At present in China, the quality of GP educational intervention studies is poor, and most faculty and researchers in GP lack training in educational intervention studies. The purpose of this paper was to introduce the process of educational intervention research in GP from design to publication, which consists of four stages with 13 steps: constructing research questions (generating research inspiration, literature review, incorporating a theoretical/conceptual framework, refining research questions), research design (trial design, intervention, outcome evaluation), research implementation (establishing a research team, obtaining research resources, applying for ethical approval, program execution), and publication and evaluation (article writing, reflection and evaluation). This paper provides research methods and ideas for educational researchers and practitioners in GP to conduct educational intervention studies, which will contribute to the generation of high-quality educational research "evidence", further improvement of the quality of GP education training, and the training of competent general practitioners.